2000
DOI: 10.1098/rspb.2000.1259
|View full text |Cite
|
Sign up to set email alerts
|

The quantitative genetic basis of offspring solicitation and parental response in a passerine bird with biparental care

Abstract: The coevolution of parental investment and offspring solicitation is driven by partly different evolutionary interests of genes expressed in parents and their offspring. In species with biparental care, the outcome of this conflict may be influenced by the sexual conflict over parental investment. Models for the resolution of such family conflicts have made so far untested assumptions about genetic variation and covariation in the parental resource provisioning response and the level of offspring solicitation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
178
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(194 citation statements)
references
References 26 publications
10
178
6
Order By: Relevance
“…There is a growing interest in the potential evolution of genetic correlations between parental provisioning and offspring solicitation as a sign of parent-offspring coadaptation (32,34). Studies have now demonstrated both positive (19,21,24) and negative (22,26) genetic correlations between female parents and their offspring. The only study to test for coadaptation between male parents and their offspring found no correlation between male care and offspring begging, despite a positive correlation between female care and offspring solicitation (21).…”
Section: Genetic and Phenotypic Correlations Within And Between The Smentioning
confidence: 99%
See 4 more Smart Citations
“…There is a growing interest in the potential evolution of genetic correlations between parental provisioning and offspring solicitation as a sign of parent-offspring coadaptation (32,34). Studies have now demonstrated both positive (19,21,24) and negative (22,26) genetic correlations between female parents and their offspring. The only study to test for coadaptation between male parents and their offspring found no correlation between male care and offspring begging, despite a positive correlation between female care and offspring solicitation (21).…”
Section: Genetic and Phenotypic Correlations Within And Between The Smentioning
confidence: 99%
“…For example, we predict that asymmetries in the reproductive strategies of males and females, which result in sexspecific genetic variation in parental responses to offspring solicitation (28), will also reflect sex differences in patterns of genetic covariation. Preliminary evidence that this may well be the case comes from studies on several species of birds demonstrating differences between the sexes in the repeatability of provisioning (13,29) and a study of great tits (Parus major) reporting a genetic correlation between parental response and offspring begging (21). It now would be valuable to test whether males and females in these species differ with respect to genetic correlations between different parental behaviors and whether these differences match any behavioral specializations in parental care.…”
Section: Genetic and Phenotypic Correlations Within And Between The Smentioning
confidence: 99%
See 3 more Smart Citations